Indexing and retrieval of free-form surfaces using self-organizing maps - MacLennan, Alexander D. (Curtin University, 2013)
This thesis describes the use of Self-Organizing Maps in combination with unique curvature based feature combinations and various training data sets as a clustering function to describe free-form surfaces. Our descriptor was successfully used as the basis of techniques that segmented, indexed and retrieved free-form surfaces represented as triangulated meshes.